Community-based sustainable rattan conservation: a case study in Lore Lindu National Park, Central Sulawesi - HAMZARI HAMZARI (Biodiversitas Journal of Biological Diversity, 2011)
Hamzari (2011) Community-based sustainable rattan conservation; a case study in Lore Lindu National Park, Central Sulawesi. Biodiversitas 12: 241-245. The following research study focused on community-based rattan conservation and was conducted in a community located in the buffer zone of Lore Lindu National Park. The aims of the study were to generate a model for communitybased rattan conservation and estimate the economic value of rattan management for the community. The results were expected to provide justification for the development of rattan management systems and strategies. The research was conducted using a combination of community education and evaluation of educational outputs. As a result, the research may be characterized as descriptive experimentation with a participative approach of andragogy. Data was collected through the employment of questionnaires, interviews, PRAs, and FGD techniques. Data were analyzed using quantitative and qualitative analysis. Based on result of analysis, inferential that community asses the effort of rattan conservation as a positive effort and its development requires additional support. The community has a desire to conduct efforts of rattan conservation continuously. The forms of rattan conservation that can be developed are rattan cultivation and selective rattan harvesting. The research developed conservation models in collaboration with rattan farming groups and involving community forestry approaches.